2005
DOI: 10.1007/s00167-005-0656-3
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical delay of the knee extensor muscles is not altered after harvesting the patellar tendon as a graft for ACL reconstruction: implications for sports performance

Abstract: Although the scar tissue, which heals the donor site defect, has different elasticity from the neighbouring patellar tissue, it remains unclear if this scar tissue can lead to the changes of the electromechanical delay (EMD) of the knee extensor muscles. If such changes do exist, they can possibly affect both the utilization of the stored energy in the series elastic component, as well as the optimal performance of the knee joint movement. The purpose of this study was to investigate the influence of harvestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
2
22
0
2
Order By: Relevance
“…The duration of the EMD is related to the velocity of force transmission from the muscle to the bone to which it attaches. 9 Although findings have been inconsistent, it has been previously reported that there is delayed onset of muscle activity in the VMO relative to the VL in individuals with PFPS. 4,18 Our data also suggest that altered VMO and VL mechanics may exist in patients with PFPS, which raises the possibility that unequal EMDs, when longer in the VMO relative to the VL, may contribute to inefficient patellar movement and thus abnormal patellar tracking.…”
Section: Discussion Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of the EMD is related to the velocity of force transmission from the muscle to the bone to which it attaches. 9 Although findings have been inconsistent, it has been previously reported that there is delayed onset of muscle activity in the VMO relative to the VL in individuals with PFPS. 4,18 Our data also suggest that altered VMO and VL mechanics may exist in patients with PFPS, which raises the possibility that unequal EMDs, when longer in the VMO relative to the VL, may contribute to inefficient patellar movement and thus abnormal patellar tracking.…”
Section: Discussion Tmentioning
confidence: 99%
“…24 Several researchers have reported that EMD is a component of protective reflexes and is related to athletic performance. 9,25,27 The shorter the EMD, the faster the muscle force transmission and the better the performance and protective reflex.…”
mentioning
confidence: 99%
“…Thus, the following epochs were utilized: 1) −200ms to −50 ms (preparatory reactions, APA1), 2) −50ms to +100ms (anticipatory reactions, APA2), 3) +100ms to 250 ms (compensatory reactions, CPA1), and 4) +250ms to 400 ms (compensatory reactions CPA2). Note that the duration of each of four epochs was the same (150 ms) as the duration of the epochs used to analyze the EMG signals (Santos et al 2009), however, the starting point of each epoch was shifted 50 ms towards T 0 to account for the electromechanical delay (Cavanagh and Komi 1979; Vint et al 2001; Georgoulis et al 2005; Rocchi et al 2006). This shift was applied to account for the kinetic and kinematic changes produced by the muscular activity that occurred before the pendulum impact (APAs) (Santos et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been shown that electromechanical delay of the quadriceps muscles is not altered in persons who have undergone ACLR. 32 Nonetheless, the use of generic values may have limited the accuracy of our muscle force and knee loading calculations. Most muscle contractile parameters are difficult to measure in vivo, and are often estimated through a mathematical optimization procedure.…”
mentioning
confidence: 99%